Traditionalist muslim in 2019 presidential election: explaining the Islamic movement in Pasar Kliwon district of Surakarta City / Muhammad Alif Alauddin and Khalis Asyifani - Alauddin, Muhammad Alif; Asyifani, Khalis (Academy of Contemporary Islamic Studies (ACIS), 2020)
In dealing with Presidential election, Muslim's vote remains to be the big object to both president candidates. Surakarta is the city known for Islam political revival through the establishment of Sarekat Dagang Islam (SDI or Islamic Trading Union) in 1912 as the first organization to fight against colonialism and imperialism in Indonesia. Considering structural functionalism theory, this paper empirically studied the condition of traditional community, including their habit, decorum, and political preference related to political participation. This research aimed to explore the traditionalist Muslim's on Islamic politic knowledge in general election and their role in influencing swing voters and suppressing absenteeism rate. This research employed qualitative method with case study approach using total sample, Muslims of Pasar Kliwon, Surakarta taken using stratified random sampling technique. It is useful to see the real life phenomenon in Pasar Kliwon Sub District where this study was conducted. The result of research shows that traditionalist Moslems have similar political preference. They are very exclusive in identity as a community but is very opened all at once in socializing and accepting other Islam ideology and cultural difference. This research also revealed that they influence the people (community) in political election through religious practices like sermon. This research contributes to social-political research in describing the role of traditional Islam community affecting the political process considerably.